The Evolution of Seismic Design Provisions in Indonesia's National Bridge Code - Veby Citra Simanjuntak; Iswandi Imran; Muslinang Moestopo; Herlien D Setio (Journal of Engineering and Technological Sciences, 2022)
To accommodate increased seismic hazards in Indonesia, provisions regarding structural details on seismic regulations have been tightened. In this paper, the variations in seismic hazard and detailing requirements from bridge code era before 1990 to the present was provided. To examine the bridge performance, pushover analysis was carried out based on the latest bridge code SNI 2833:2016/Seismic Map 2017. From the analysis results, the performance of older bridges would typically be less than more recently designed structures.  The performance level of the bridge in the era before SNI 2833:2016/Seismic Map 2017 will be Operational-Life Safety (LS) whereas the performance level of the bridge designed with SNI 2833:2016 will be Elastic – Operational. Referring to NCHRP 949 for bridge performance level evaluation, results show that the performance level of the bridge still satisfies the requirement, which is Life Safety under upper-level earthquake. Therefore, the existing bridge shows adequate capacity under the current seismic load Seismic Map 2017 (7% probability of exceedance in 75 years (RP= 1000 years)). Evaluation of seismic vulnerability needs to be done to ensure the safety of the existing bridges in Indonesia, most of which are located in earthquake-prone areas, especially those that were designed with older version regulations.